Imunomodulator Activity of Alginate Oligosaccharides from Alginate Sargassum crassifolium - Subaryono Subaryono; Rosmawati Perangiangin; Maggy Thenawidjaja Suhartono; Fransiska Rungkat Zakaria (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Alginate oligosaccharides (AOS) are oligosaccharides produced from depolimerization of the alginate polymer, and is reported to have various biological activities. The study aims is to determine the effect of AOSproduction conditions and their effects on products and its activities as an immunomodulatory compound. Production of alginate oligosaccharides (AOS) enzymatically carried out with the help of alginate lyase enzyme produced from the bacterium Bacillus megaterium S245. Variation of incubation time is 2, 4, 6 and 8 hours at concentrations of alginate lyase enzyme addition of 25, 50, 75 and 100U. Treatment of enzyme concentration and the duration of incubation in the production of AOS produces a degree of polymerization (DP) 2-7. In vitro activity test showed AOS is have ability to induce cell proliferation of human lymphocytes.This type of cell lymphocytes proliferation induced by AOS is a CD 8 cells or cytotoxic T cell and non cell CD4 / CD8. AOS production conditions with the addition of alginate lyase enzyme 50 U and incubation period 2 hours has produce AOS with the highest index of lymphocyte proliferation  117.6+3.6% or an increase of 43.24% compared to the native alginat polymer.